Health Information and Decision Making Preference on Disease Treatment - Bin Mohamed Ali, Muhammad Hasif; Syukriani, Yoni; Sulthana, Bambang (Althea Medical Journal, 2015)
Background: Medical decision making is a complex cognitive process of choosing in establishing a diagnosis and selecting a management option in the context of healthcare. Patients may desire to take part in obtaining and exchanging information, discussing over options and making the final decisions about treatment and or care. The focus of the study was to identify the health information and decision making preference on diseases treatment.Methods: A descriptive study was conducted to 110 respondents from Hegarmanah Village, Sumedang, Indonesia, aged 18â65 years old who had the experience in consulting doctors for their medical problems. This study was carried out during the period of September to October 2013. The respondents were selected using random stratified sampling. A tested questionnaire, consisted of 2 sections, was used to collect the data. The collected data were presented using frequency tabulation.Results: Most of the respondents preferred to be offered choices and asked for their opinions by their doctors. Furthermore, 55.45% preferred to rely on physicians for medical knowledge and 93.64% agreed that they had rights in getting all the information on their medical problems, so they submitted their decision to the doctors for care or treatment.Conclusions: This study shows that preference of the patients varies with regard to how much patients want to participate as one, which may have different preference for different components of the decision making process, yet there is a shift of paradigm from paternalistic toÂ  collaborative decicion making between doctor and patient. [AMJ.2015;2(4):463â8]Â DOI:Â 10.15850/amj.v2n4.628